Spontaneous spreading depolarizations originate subcortically in a novel mouse model of familial hemiplegic migraine type 2 - Nico A. Jansen; Chelsey Linnenbank; Maarten Schenke; Rob A. Voskuyl; Maria S. Jorge; Georgii Krivoshein; Cor Breukel; Margot M. Linssen; Jill W.C. Claassens; Conny Brouwers; Sandra H. van Heiningen; Anders Heuck; et al. (Neurobiology of Disease)
The mechanisms of initiation of spreading depolarization (SD) are understudied due to a paucity of disease models with spontaneously occurring events. We here present a novel mouse model of familial hemiplegic migraine type 2 (FHM2), expressing the missense T345A-mutated α2 subunit of the Na+/K+ adenosine triphosphatase pump (Atp1a2T345A). Homozygous Atp1a2T345A mice showed regular spontaneous SDs that exhibit a diurnal rhythm and typically originate from the hippocampus. Heterozygous Atp1a2T345A mice rarely exhibited spontaneous SDs and, for electrically induced SDs, only showed an increased propagation speed, whereas homozygotes showed both increased propagation and decreased threshold. Remarkably, despite hippocampal hyperexcitability, spontaneous SDs in Atp1a2T345A mice were only rarely associated with epileptic behavior, and seizure expression during kindling was decreased. Spontaneous SDs could be prevented by modulation of persistent sodium currents. Hippocampal SDs occurred in the presence of an NMDA-receptor antagonist, but these events did not reach the cortex, suggesting that initiation and propagation of SD depend on different mechanisms in this model.